Pengaruh Leverage, Growth Opportunity dan Firm Size Terhadap Keputusan Hedging Pada Perusahaan Sektor Cosumer Goods Industry Yang Terdaftar Pada BEI - Vera Nanda; Darmawati Muchtar; Halida Bahri (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This study aims to examine the effect of leverage, growth opportunity, and firm size on hedging decisions by consumer goods industry firms. The sample of this study was 28 firms for the period 2016-2020. This study used balance panel data with 140 observations. The method of this study is Binary logit estimation, in which the dependent variable is a dummy with 1,0 for the firm using hedging and otherwise. This study finds that leverage positively affects hedging decisions but is not significant. The rising debt would lead the companies to hedge asset instruments. Growth Opportunity has a different effect, whereas growth opportunity has a negative and insignificant effect. The findings do not correspond to the hypothetical expectation. They are also not in line with the theory, which states that there is a linear relationship between investment opportunities and hedging decisions. The findings do not support the expected hypothesis. They are also not in line with the theory, which states that there is a linear relationship between investment opportunities and hedging decisions. Furthermore, the effect of firm size on hedging decisions is positive and significant. The larger firm size would lead increase in the hedging decision in Indonesia. The implication is that the company's management must focus more on the impact of investment opportunities with the company's policy of conducting low hedging. A higher investment opportunity has a higher risk of getting a return.